Market players a guide to the institutions in today's financial markets - Rolland, Gail. (Chichester, West Sussex : Wiley, 2011)
"No longer are the capital markets driven by the big investment houses and fund managers. Instead, private banks, insurance houses, hedge funds, sovereign wealth funds and a range of boutique investment managers, regional institutions and brokers all operate and interact to form the bedrock of the global capital markets, and all practitioners need to understand the linkages, objectives and functions of these institutions to understand how the markets really work. How the Markets Work provides a complete roadmap to the institutions and intermediaries operating in today's global financial landscape. The book has arisen out of the authors 25+ years working and training in the capital markets. While there is a large amount of literature dedicated to financial market products and how the market works, few, if any look at the institutions themselves. This book will look at all the institutions operating today, illustrating what they are, how they work, how they interact and importantly, their motivation. It will explain the core financial market business of these institutions, and consider how they have become the firms that we see today, providing readers with a clear understanding of which market sectors are likely to see the most involvement from the different types of institution and, importantly, why they are involved in these market areas. The author will bring these institutions to life through a number of case studies such as AIG and Northern Rock, illustrating why a particular institution, plays such a key role in the markets, and what happens when something goes wrong. "--
"This book will look at all the institutions operating today, illustrating what they are, how they work, how they interact and importantly, their motivation"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Financial institutions; Banks and banking; Financial services industry; Capital market; Electronic books